Electron-transfer chemistry of the iron-molybdenum cofactor of nitrogenase: delocalized and localized reduced states of FeMoco which allow binding of carbon monoxide to iron and molybdenum. - Pickett, C; Vincent, K; Ibrahim, S; Gormal, C; Smith, B; Best, S (2003)
The electron-transfer chemistry of the isolated iron-molybdenum cofactor of nitrogenase (FeMoco) has been studied by electrochemical and spectroelectrochemical methods. Two interconverting forms of the cofactor arise from a redox-linked ligand isomerism at the terminal iron atom; this is attributed to rotamerism of an anionic N-methyl formamide ligand bound at this site. FeMoco in its EPR-silent oxidised state is shown to undergo three successive one-electron transfer steps. We argue that the first and second redox processes are associated with electron-transfer delocalised over the iron-sulfur core of the cofactor, whilst the third irreversible process is localised on molybdenum. This is strongly reinforced by spectroelectrochemical studies under (12)CO and (13)CO which reveal two independent carbon monoxide binding sites that are specifically associated with the second (iron core) and third (molybdenum) electron-transfer processes and which give rise to terminal nu((12)CO) bands at 1885 and 1920 cm(-1) respectively. Moreover, in parallel with earlier studies on the enzyme system, it is shown that at low CO concentration, carbon monoxide binds to the cofactor in bridging modes, with nu(CO) bands at 1835 and 1808 cm(-1) that are interconverted by single-electron transfer. Importantly we show that the contentious overall 2e difference in the assignment of the metal oxidation levels in the resting state of the enzyme-bound cofactor, arising from analysis of (57)Fe ENDOR and Mössbauer data, can be resolved in the light of the electron-transfer chemistry of the isolated cofactor described herein.